A Proposal for Research Involving New Biomarkers of Hypertension, Lifestyle, and Environmental Exposure - Angelika Edyta Charkiewicz (Current Issues in Molecular Biology)
The constant monitoring of the population’s diet and assessment of occupational exposure and environmental impacts are the key to determining health risks and understanding the factors contributing to potential abnormalities in developing lifestyle diseases. Extensive long-term lifestyle monitoring studies can provide data on population health risks, including the most common cardiovascular diseases like hypertension. This paper presents research recommendations for future researchers and doctors to improve the diagnosis of hypertension and targeted, personalised treatment. The research proposal includes a lifestyle study, a diagnostic panel with new biomarkers, and an environmental exposure assessment of men working in the metallurgical industry. New developments and improved interventions are constantly being sought, including new biomarkers with high diagnostic utility for cardiovascular diseases like hypertension. This should enable early diagnosis, and consequently allow for appropriate and, most importantly, personalised therapy, and prevent an increase in CVD deaths. Only the effective diagnosis, treatment, and monitoring of hypertension can reduce the risk of developing diseases associated with hypertension. I propose that several new parameters (NO, cfDNA, MPO, PCSK9, MyBPC3, microRNA, TAS, Pb, and Cd) with prognostic and/or predictive potential should be included in screening to confirm the need for the extensive testing of middle-aged men by healthcare professionals due to the risk of hypertension.